Akibat Hukum terhadap Keterlambatan Penyerahan Sertifikat Tanah oleh Kantor Pertanahan Kota Bandung dalam Perspektif Hukum Perdata - Vriscilla Akasya Putri Hidayat; Dedy Hernawan (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Land registration aims to provide legal certainty and legal protection to land rights holders through the issuance and delivery of certificates as strong evidence. However, in practice, delays in the delivery of land certificates are still encountered at the Bandung City Land Office. Research findings indicate that these delays are caused by incomplete administrative requirements, challenges in transitioning from analog to electronic certificates, and disruptions in the electronic system. These delays result in the postponement of the exercise of the public’s civil rights, such as sales and purchase transactions, the establishment of liens, and credit applications. Therefore, service effectiveness must be improved to ensure legal certainty for the public.